Nanofiber Research Reaching New Heights - Muzibur Rahman, Mohammed; Asiri, Abdullah M. (IntechOpen, 2016)
This book titled Nanofiber Research - Reaching New Heights contains a number of latest research results on growth and developments on material fibers in nanoscale. It is a promising novel research area that has received a lot of interest in recent years. This book includes interesting reports on cutting-edge science and technology related to synthesis, morphology, control, self-assembly and prospective application of nanofibers. I hope that the book will lead to systematization of nanofiber science, creation of new nanofiber research field and further promotion of nanofiber technology. This potentially unique work offers various approaches on the implementation of nanofibers. As it is widely known, nanotechnology presents the control of matter at the nanoscale and nano-dimensions within few nanometers, whereas this exclusive phenomenon enables us to regulate and control novel applications with nanofibers. This book presents an overview of recent and current nanofibers fundamental, significant applications and implementation research worldwide. It examined the methods of nanofiber synthesis, types of fibers used and potential applications associated with nanofiber researches. It is an important booklet for research organizations, governmental research centers, academic libraries and R&D affianced in recent research and development of nanofibers.